2017
DOI: 10.4103/jiaps.jiaps_233_16
|View full text |Cite
|
Sign up to set email alerts
|

Type V congenital pouch colon: An extremely rare variant of anorectal malformations

Abstract: Type V is the rarest form of congenital pouch colon with only four cases reported till date. We report this anomaly in a 6-month-old boy. He was managed successfully with excision of distal pouch and coloplasty of proximal pouch along with abdominoperineal posterior sagittal anorectoplasty. We recommend preservation of proximal pouch in such cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…In this classification 4 types can be described, type I: normal colon is not present and the terminal ileum opens into the abnormal colon pouch, type II: the terminal ileum opens to the cecum which in turn opens to the colonic pouch, type III: there is a significant normal colonic segment between the ileum and the colonic pouch, and type IV: the colon is almost normal and the pouch involves the sigmoid and the rectum. Some authors describe a 5th type which is extremely rare and only few cases had been reported which consists of 2 colonic pouches with an intervening normal colonic segment [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…In this classification 4 types can be described, type I: normal colon is not present and the terminal ileum opens into the abnormal colon pouch, type II: the terminal ileum opens to the cecum which in turn opens to the colonic pouch, type III: there is a significant normal colonic segment between the ileum and the colonic pouch, and type IV: the colon is almost normal and the pouch involves the sigmoid and the rectum. Some authors describe a 5th type which is extremely rare and only few cases had been reported which consists of 2 colonic pouches with an intervening normal colonic segment [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…[1] Type V also has been described in the literature. [23] Type I is the most severe form and Type IV is the least. In males, the pouch usually terminates in a colovesical fistula just proximal to the bladder neck.…”
Section: Introductionmentioning
confidence: 99%
“…Классификация Narasimharao «ректального мешка»: CPC (congenital pouch colon) -врожденный «ректальный мешок»; SMA (Superior mesenteric artery) -верхняя брыжеечная артерия; UB (Urinary bladder) -мочевой пузырь; CVF (Colovesical fistula) -мочеполовой свищ[23] В 2008 году в классификацию был добавлен пятый вариант. Аномалия развития представляет собой несколько кишечных «мешков», между которыми находится нормально сформированный участок ободочной кишки[24].…”
unclassified